Continuous isoprene measurements in a UK temperate forest for a whole growing season: effects of drought stress during the 2018 heatwave - Ferracci, Valerio; Bolas, Conor G.; Freshwater, Ray A.; Staniaszek, Zosia; King, Thomas; Jaars, Kerneels; Otu‐Larbi, Frederick; Beale, John; Malhi, Yadvinder; Waine, Toby W.; Jones, Roderic L.; Ashworth, Kirsti; et al. (American Geophysical Union (AGU), 2020)
Isoprene concentrations were measured at four heights below, within and above the forest canopy in Wytham Woods (UK) throughout the summer of 2018 using custom-built gas chromatographs (the iDirac). These observations were complemented with selected ancillary variables, including air temperature, photosynthetically active radiation (PAR), occasional leaf gas exchange measurements and satellite retrievals of normalized difference vegetation and water indices (NDVI and NDWI). The campaign overlapped with a long and uninterrupted heatwave accompanied by moderate drought. Peak isoprene concentrations during the heatwave-drought were up to a factor of 4 higher than those before or after. Higher temperatures during the heatwave could not account for all the observed isoprene; the enhanced abundances correlated with drought stress. Leaf-level emissions confirmed this and also included compounds associated with ecosystem stress. This work highlights that a more in-depth understanding of the effects of drought stress is required to better characterize isoprene emissions.
Keywords: long-term measurements; drought stress; BVOCs; biosphere-atmosphere interactions; Isoprene